2009
DOI: 10.1177/000313480907500812
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Inaccessible Arteriovenous Fistulas in Obese Patients: A Review of 132 Brachiocephalic Fistulas

Abstract: The two main factors leading to a functional fistula are maturity and accessibility. The aim of this review was to describe a technique of superficialization for inaccessible brachiocephalic fistulas, and to identify the patients that benefit from superficialization. One hundred and thirty-two brachiocephalic arteriovenous fistulas developed from November 2003 to December 2006 were reviewed for primary maturation. In the mature group, patients were evaluated for fistula accessibility. Inaccessible fistulas wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The majority of these patients were female. 28 We did not observe a difference in BMI between males or females. However, the body fat in men is differently distributed compared to women and it may be that more pronounced subcutaneous fat in the arms of women influenced the selection of the AV fistula.…”
Section: Discussionmentioning
confidence: 49%
“…The majority of these patients were female. 28 We did not observe a difference in BMI between males or females. However, the body fat in men is differently distributed compared to women and it may be that more pronounced subcutaneous fat in the arms of women influenced the selection of the AV fistula.…”
Section: Discussionmentioning
confidence: 49%
“…The population group was predominantly female (78%) and had an elevated BMI (BMI 31 kg/m 2 ). All superficialised fistulae supported haemodialysis post operatively (9). Weyde et al performed 71 radio-cephalic superficialisation procedures on a patient population with a mean BMI of 34.6 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…We wish to point out, however, that while the three groups of patients were similar in as far as diabetes mellitus and cardiac conditions are concerned, the group of patients for which proximal AVF were created included seven obese patients (22%) with a body mass index (BMI) >30, whereas obesity was virtually absent in the other two groups of patients. It appears important to underline this aspect in light of recent studies that have identified obesity as a condition capable of influencing AVF survival (11) because of the likelihood of soft-tissue compression of the venous outflow (12) and have observed that the superficialization of the vein is a means of salvaging the access in such circumstances (13).…”
Section: Discussionmentioning
confidence: 99%